The Effect of Token Economy in Reducing Addiction to Playing Online Games in Psychology Students at UIN Malang - Ikhwan Arief Maulana Hsb; Muhammad Jamaluddin (Journal of Science and Research, 2025)
This study aims to test the effectiveness of the token economy method in reducing online gaming addictionamong college students. The study uses a single subject design with an A-B design, involving one 21-year-old subject who, in this case, exhibited five of the six indicators of online gaming addiction, namelysalience, euphoria, conflict, tolerance, relapse, and reinstatement. The intervention was conducted over7 days using a token method in the form of coins, which were later exchanged for cash rewards, basedon a reduction in the intensity of online gaming from a daily baseline of 5 hours. The results of this studyshowed a significant decrease in the intensity of online gaming, with a final percentage of 95%, from anaverage of 5 hours of online gaming activity to only 15 minutes per day. Additionally, subjects exhibitedpositive behavioral changes, such as increased social activity and reduced solitary behavior. Ultimately,this study serves as evidence that the token economy method remains effective as a behavioralmodification technique for addressing online gaming addiction among students and can serve as arelevant intervention strategy to be applied in the current digital era.